Multi-order PID controller design for active anti-roll suspension system - Mohamed Jamil, Fathiah (2017)
This paper focusing on investigation of multi-order Proportional-Integral-Derivative (MOPID) controller for active anti-roll suspension system in order to provide ride comfort and stability while handling the vehicle on uneven road surface. Development of the MOPID has been arranged and tested on 4DOF half car model in order to increase ride comfort and improve vehicle controllability. MOPID work in a separate loop where the outer loop increase the disturbance from the road (input) and the signal that has been sent to the active suspension system through inner loop that controlled by force actuator that act in reducing the unnecessary vehicle motion. The performance comparison has been made between passive suspension and active anti roll suspension by using Matlab/Simulink (active suspension) and CarSim work as a reference for simulation studies of passive suspension. The different can be seen after MOPID has been applied to the active anti roll suspension system. Its shows that MOPID create a better system which work much more better by providing vehicle stability, good controllability and ride comfort. It’s also give an improvement on vehicle handling in term of body displacement and body roll. Thus, the development of this controllers is important besides its structure is simple and easy in practice.